The Effect of Effleurage Technique Back Massage Using Lavender Aromatherapy Oil on Post-Partum Breast Milk Production - Yuni Herdiyani; Nurul Isnaini; Vida Wira Utami; Suharman Suharman (Universitas Malahayati Lampung, 2024)
ABSTRACT Lack of stimulation of the hormones prolactin and oxytocin can result in not achieving exclusive breastfeeding, psychological stress, decreased milk production in the first days after delivery. This hormone plays a role in the smooth production of breast milk. Attempts to stimulate the hormones prolactin and oxytocin can be done by back massage with the effleurage technique using lavender aromatherapy oil on post-partum breast milk production. This study aims to determine the effect of back massage using the effleurage technique using lavender aromatherapy oil on post-partum breast milk production at the Way Nipah Community Health Center in 2023. The research method used is quantitative with a pre-experimental design, one-group pretest-posttest. The sampling technique used proportional random sampling. The research was conducted in February-July 2023 at the Way Nipah Community Health Center in 30 people. Data analysis used the Wilcoxon test. The average breast milk production before the intervention was 5.37 ml with a standard deviation of 2.48, the minimum value was 0.0 and the maximum value was 10.0. The average breast milk production before effleurage technique back massage with lavender aromatherapy oil is between 4.44 to 6.29. The average breast milk production after the intervention was 77.0 ml, with a standard deviation of 9.79. The smallest value was 50.0, and the maximum value was 90.0. From the interval estimation results, it can be concluded that 95% believed that the average breast milk production after the effleurage technique back massage with lavender aromatherapy oil was between 73.34 and 80.65. There is an effect of back massage using the effleurage technique back massage with lavender aromatherapy oil on the post-partum breast milk production at the Way Nipah Community Health Center in 2023. Community Health Center can be used to support breastfeeding their babies and assist in applying effleurage technique back massage to help breast milk production. Keywords: Effleurage Back Massage, Lavender Aromatherapy Oil, Breast Milk Production, Post-partum ABSTRAK Kurangnya rangsangan hormon prolaktin dan oksitosin dapat mengakibakan tidak tercapainya pemberian ASI eksklusif, stress psikologis, penurunan produksi dan pengeluaran ASI pada hari-hari pertama setelah melahirkan. Hormon tersebut berperan dalam kelancaran produksi ASI. Usaha untuk merangsang hormon prolaktin dan oksitosin dapat dilakukan pijat punggung teknik effleurage menggunakan minyak aromaterapi lavender terhadap produksi ASI postpartum. Penelitian ini bertujuan untuk mengetahui pengaruh pijat punggung teknik effleurage menggunakan minyak aromaterapi lavender terhadap pengeluaran ASI ibu post-partum di Puskesmas Way Nipah tahun 2023. Metode penelitian yang digunakan yaitu kuantitatif dengan pre-experimental design, one-group pretest-posttest. Teknik pengambilan sampel menggunakan proportional random sampling. Penelitian dilakukan pada Februari-Juli 2023 di Puskesmas Way Nipah pada 30 orang. Analisis data menggunakan uji Wilcoxon. Rata-rata produksi ASI sebelum intervensi adalah 5,37 ml dengan standar deviasi 2,48, nilai minimum yaitu 0,0 dan nilai maksimum adalah 10,0. Rata-rata produksi ASI sebelum pijat punggung teknik effleurage dengan minyak aromaterapi lavender adalah antara 4,44 sampai 6,29. Rata-rata produksi ASI setelah intervensi adalah 77,0 ml, dengan standar deviasi 9,79. Nilai terkecil adalah 50,0, dan nilai maksimum adalah 90,0. Dari hasil estimasi interval dapat disimpulkan bahwa 95% percaya bahwa rata-rata produksi ASI setelah pijat punggung teknik effleurage dengan minyak aromaterapi lavender adalah antara 73,34 dan 80,65. Ada pengaruh pijat punggung teknik effleurage menggunakan minyak aromaterapi lavender terhadap pengeluaran ASI ibu post-partum di Puskesmas Way Nipah Tahun 2023. Bagi Puskesmas dapat dijadikan sebagai bahan untuk memberi dukungan kepada ibu untuk menyusui bayi dan dapat membantu ibu dalam menerapkan pijat punggung effluarge dalam membantu produksi ASI. Kata Kunci: Pijat Punggung Effluarge, Minyak Aromaterapi Lavender, Pengeluaran ASI, Post-partum